Higher order analysis of time-resolved proton radiographs. (23rd August 2019) - Doolan, P J; Bentefour, E H; Testa, M; Cascio, E; Sharp, G; Royle, G; Lu, H-M
Abstract: We demonstrate the potential of analyzing the higher order moments of time-resolved proton radiographic signals to generate images that show internal structures not visible in standard water-equivalent thickness (WET) images. Using a single detector distal to the patient, proton transmission images were acquired using a scintillating screen coupled to a CCD camera, with the beam range modulated using a small dedicated range modulator wheel. The variation of dose with time to a given pixel is referred to as the dose rate function, DRF. The width of the DRF can be correlated to the WET of the material and the shape of the DRF is representative of heterogeneities. The shape of the DRF can be described by the higher order functions, skewness and kurtosis. A number of phantoms were imaged to assess the usability of the higher order images: the Gammex 467 phantom; a step phantom; thin plastic squares at shallow and deep depths of solid water; an anthropomorphic foot phantom; and an anthropomorphic head phantom. In all cases the higher order moment images highlighted regions of heterogeneities, and in many cases such heterogeneities were not visible in the standard WET image. Such heterogeneities could be either composed of changes in thickness of the same material or changes due to different materials. As well as having the potential as a useful imaging protocol in its own right, the higher order images offer the potential to discriminate which pixels can be relied on in the WET map and which pixels are likely to be subject to range mixing. In this work we demonstrate that these higher order images can be used to create a mask to remove pixels that are potentially subject to range mixing and potentially have unreliable WET values.